Geographic Development, Macroeconomic Stability, and Civil Rights Defense - ALIYEV, Zakir H; ALLAHVERDIYEV, Dagbeyi; BEKIROVA, Vusale (Journal of Political And Legal Sovereignty, 2024)
Purpose:In the article, opinions about the sustainable socioeconomic progress of Azerbaijan in the geopolitical relations with the world's countries, macroeconomic stability criteria, and political-economic perspective possibilities are explained.Methodology:Methodologically innovative policy has interpreted economic criteria in the concept of national security of Azerbaijan as the essence of socioeconomic well-being. Thus, several criteria have been defined to ensure sustainable socioeconomic progress: Fiscal and free currency regime, formation of monetary policy, Development of human capital, Quality criteria in economic problems, Macroeconomic efficiency, and Socioeconomic equality.Findings:The overall economic potential of Azerbaijan, national economic progress, and directions for increasing state support for its sustainability have been analyzed. Thus, the experience and modern situation of the world's countries in political-economic relations and socioeconomic progress, macroeconomic stability, protection of civil rights, and civil welfare of the state were investigated.Implication:The country's geopolitical progress, macroeconomic stability, and civil rights protection are stipulated as fundamental guarantees of socioeconomic progress. For this reason, the main criterion of socioeconomic security is macroeconomic stability, elimination of unemployment, and creation of new jobs.